Bahasa Indonesia: VARIASI BAHASA PADA DESKRIPSI SINGKAT (CAPTION) AKUN INSTAGRAM DOSEN FAKULTAS TARBIYAH IAI AL-QOLAM MALANG - Malikha, Usrin (JURNAL PUSAKA : Media Kajian dan Pemikiran Islam, 2022)
This study examines the use of the types of abbreviations and the abbreviation process in the short description (caption) of the Tribun News Instagram account in January 2022. The purpose of this study is to describe the types of abbreviations and the abbreviation process in the brief description (caption) of the Tribun News Instagram account in January 2022. This study used descriptive qualitative method. The data for this research are all words, phrases and abbreviated sentences contained in the short description (caption) of the Tribun News Instagram account. The source of this research data is a brief description (caption) of the Tribun News Instagram account on January 1-January 31. The instrument used in this research is the human instrument (the researcher himself). The technique of extracting data is by reading the caption of the Tribun News Instagram account and grouping it according to the type and process of abbreviation. The data analysis technique used is the Agih method. The validity of this research technique is by means of interrater and intra rater. Based on the results of the study, it was found that in the Tribun News Instagram account there were 146 containing abbreviations and 164 abbreviation processes. First, there are 5 types of abbreviations, namely abbreviations, fragments, acronyms, contractions and letter symbols. Second, there are four abbreviation processes, namely abbreviations: preservation of the first letter of each component, preservation of the first letter by removing conjunctions, prepositions, reduplications and prepositions, articulation and words, preservation of the first two letters of a word, preservation of the first three letters of a word. , preservation of the first four letters of a word, preservation of the first and last letters of a word, and preservation of the first and last letters of the first syllable and the first letter of the second syllable. Fragmentation: fragmentation of the first syllable of a word, preservation of the first three letters of a word, preservation of the first four letters of a word, and partial removal of a word. Acronyms: perpetuation of the first syllable of each component, preservation of the first syllable of the first component and preservation of the whole word, preservation of the first three letters of each component, preservation of the first two letters of the first component and the first three letters of the second component with conjunctions, preservation of the first two letters of the first component and three letters First the second component, the sharing of letters and syllables that are difficult to formulate. Symbol of letters: symbol of letters that mark the currency. Key words: abbreviation; Instagram; types of abbreviation; linguistic; acronym.